Syntactic Analysis of Surah Qaf English Translation by Muhammad Taqiudin Al Hilali and Muhammad Muhsin Khan - Nur Azizah; Yazid Basthomi; Arif Subianto (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: The present research is an analytical study referring to the Quranic English translation. It specifically aims at analyzing the constituent structure of sentence types in Surah Qaf English translation by Muhammad Taqiudin Al Hilali and Muhammad Muhsin Khan. More particularly, this research sets out to identify the sentence types found in the translation and analyze them at the syntactic level. The data for this research are taken from al-quran.info.com, the trusted site for Qur’an online translation and commentary. The method used in this research is descriptive qualitative. Based on the analysis, the findings indicate that four sentence types (declarative, imperative, exclamatory, and interrogative) appear in the Surah Qaf English translation with different number of occurrences. This research is also conducted to find out the constituent structure of each sentence type. The results also show that each sentence type has a distinctive pattern of constituent and grammatical structure. Keywords: syntactic analysis, sentence types, quranic translation Abstrak: Penelitian ini merupakan sebuah studi analitik yang merujuk pada terjemahan Al Quran dalam Bahasa Inggris. Penelitian ini bertujuan untuk menganalisis struktur konstituen tipe-tipe kalimat yang ada pada terjemahan Surah Qaf dalam Bahasa Inggris oleh Muhammad Taqiudin Al Hilali dan Muhammad Muhsin Khan. Singkatnya, penelitian ini bertujuan untuk mendeskripsikan dan menganalisis secara sintaksis tipe-tipe kalimat yang ditemukan di hasil terjemahan tersebut. Data penelitian ini diambil dari al-quran.info.com, sebuah situs terpercaya khusus terjemahan dan tafsir online Al Quran. Metode yang digunakan adalah metode deskriptif kualitatif. Berdasarkan hasil penelitian, terdapat empat tipe kalimat dengan frekuensi yang berbeda-beda yang ditemukan dalam hasil terjemahan Surah Qaf, antara lain deklaratif, imperatif, seruan, dan interogatif. Hasil penelitian menunjukkan bahwa tiap tipe kalimat memiliki tipe konstituen dan struktur tata bahasa tersendiri. Kata kunci: Analisis sintaksis, tipe kalimat, terjemahan Alquran